2014
DOI: 10.1177/0192623314525684
|View full text |Cite
|
Sign up to set email alerts
|

miR-208a as a Biomarker of Isoproterenol-induced Cardiac Injury in Sod2+/− and C57BL/6J Wild-type Mice

Abstract: This investigation examined microRNA-208a (miR-208a) as a potential biomarker of isoproterenol (ISO)-induced cardiac injury in superoxide dismutase-2 (Sod2(+/-) ) and the wild-type mice, and the potential sensitivity of Sod2(+/-) mice to ISO-induced toxicity. A single intraperitoneal injection of ISO was administered to age-matched wild-type and Sod2(+/-) mice at 0, 80, or 160 mg/kg. Plasma miR-208a, cardiac troponin I (cTnI), and ISO systemic exposure were measured at various time points postdose. Hearts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Interestingly, miR-208a (heart-specific miRNA) [17] and -208b were undetected in this study, although previously published studies have suggested them as new biomarkers of myocardial injury following myocardial infarction [18, 19] or isoproterenol use [5, 20, 21]. This discrepancy may be a result of a differential response of the cardiomyocytes to DOX stimuli.…”
Section: Discussionmentioning
confidence: 55%
“…Interestingly, miR-208a (heart-specific miRNA) [17] and -208b were undetected in this study, although previously published studies have suggested them as new biomarkers of myocardial injury following myocardial infarction [18, 19] or isoproterenol use [5, 20, 21]. This discrepancy may be a result of a differential response of the cardiomyocytes to DOX stimuli.…”
Section: Discussionmentioning
confidence: 55%
“…Specifically, overexpression of miR-208a resulted in increased α-MHC expression and was associated with arrhythmias, fibrosis and hypertrophy in mice[72]. Following isoproteronol-induced cardiac injury in rats, miR-208a was shown to have stable upregulation in plasma and was superior to cardiac troponins in indicating injury[73, 74]. MiR-208a was also increased in the human heart tissue of patients who died from MI[75].…”
Section: Mirnas In Heart Injury and Repairmentioning
confidence: 99%
“…However, the potential for a new drug to cause cardiotoxicity may not be detected until after clinical trials in humans have begun. In some cases, drug-associated cardiotoxicity may not be observed until after drug approval [159,160]. The potential adverse effects of cardiotoxicity are arrhythmias, hypertension, abnormal left ventricular ejection fraction (LVEF) and eventually heart failure [161].…”
Section: Mirnas In Assessment Of Drug Safetymentioning
confidence: 99%
“…In addition, miR-208 increased with a similar time course with the plasma cTnI level. Another study by Liu et al [160] compared the role of miR-208a in isoprenaline-treated wild-type C57BL/6J mice and C57BL/6J mice that were heterozygous for Sod2 (Sod2 +/- ). They concluded that increases in miR-208a detected in plasma correlated more closely with isoprenaline-induced myocardial damage than cTnI levels in plasma in both types of mice.…”
Section: Mirnas In Assessment Of Drug Safetymentioning
confidence: 99%